Translation and Transformation: English-Language Children's Literature in (Soviet) Russian Guise. Issue 1 (July 2015) - Inggs, Judith
<x xml:space="preserve">Abstract</x> This article investigates the perceived image of English-language children's literature in Soviet Russia. Framed by Even-Zohar's polysystem theory and Bourdieu's philosophy of action, the discussion takes into account the ideological constraints of the practice of translation and the manipulation of texts. Several factors involved in creating the perceived character of a body of literature are identified, such as the requirements of socialist realism, publishing practices in the Soviet Union, the tradition of free translation and accessibility in the translation of children's literature. This study explores these factors and, with reference to selected examples, illustrates how the political and sociological climate of translation in the Soviet Union influenced the translation practices and the field of translated children's literature, creating a particular image of English-language children's literature in (Soviet) Russia.